American gospel : God, the founding fathers, and the making of a nation - Meacham, Jon (New York : Random House, 2006)
Author Meacham tells the human story of how the Founding Fathers viewed faith, and how they ultimately created a nation in which belief in God is a matter of choice. At a time when our country seems divided by extremism, this book draws on the past to offer a new perspective. Meacham re-creates the history of a nation grappling with religion and politics--from John Winthrop's "city on a hill" sermon to Thomas Jefferson's Declaration of Independence; from a proposed nineteenth-century Christian Amendment to the Constitution to Martin Luther King, Jr.'s call for civil rights; from George Washington to Ronald Reagan. At the heart of the American experiment lies what Benjamin Franklin called "public religion," a God who invests all human beings with inalienable rights while protecting private religion from government interference. It is a great American balancing act, and it has served us well.--From publisher description.
Includes bibliographical references (p. [359]-387).
Keywords: Religion and politics -- United States -- History; Christianity and politics -- History -- United States; National characteristics, American; United States -- Religion; United States -- History -- Religious aspects -- Christianity